Why Do Mortality Rates for Nonvariceal Upper Gastrointestinal Bleeding Differ around the World? A Systematic Review of Cohort Studies - Vipul Jairath; Myriam Martel; Richard FA Logan; Alan N Barkun (Canadian Journal of Gastroenterology)
BACKGROUND: Discrepancies exist in reported mortality rates of nonvariceal upper gastrointestinal bleeding (NVUGIB).